Nepal’s Gen-Z Revolt and Its Implications - Bhatta, Chandra Dev (NCWA Annual Journal, 2026)
The Gen-Z revolt on September 8 and 9, 2025, in Nepal has not only shaken the raison d’être of the Nepali state but also changed the political landscape. The two-day revolt not only led to the death of 76 people, and burned down administrative buildings such as the central secretariat, parliament, presidential palace, supreme court, police booths, and local administrative offices throughout the country, but it also tore apart the confidence of Nepali citizens in the state and its institutions. Protestors selectively burned down houses of the political leaders and high-ranking officials. Top political leaders – who were in power for decades - were booted out. The then Prime Minister KP Sharma Oli and his cabinet had to resign. The state institutions virtually collapsed. Billions of rupees’ worth of property was gutted. In fact, Nepal lost around 5% of its total Gross Domestic Product (GDP) within less than 40 hours (RSS, 2025). Nepal’s parliament was dissolved, and former Chief Justice of the Supreme Court, Sushila Karki, became the interim Prime Minister with the support of Gen-Z leaders. Karki’s government was entrusted to hold the national election on March 5, 2026. With these changes, the constitution of Nepal, which was drafted through the constituent assembly, was put on a state of virtual abeyance. Although many constitutional experts argued that the interim government was constituted as per Article 61 of the current constitution, the nearest justification in that regard would have been the ‘doctrine of necessity’ that the President can exercise. This article aims to explore the factors that led to the Gen-Z revolt and its implications for Nepal in the future.